2004
DOI: 10.1007/s00439-004-1136-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased amount of the angiotensin-converting enzyme (ACE) mRNA originating from the ACE allele with deletion

Abstract: The insertion/deletion (I/D) polymorphism in intron 16 of the angiotensin-converting enzyme (ACE) gene is involved in the development of cardiovascular diseases. We compared the ACE mRNA expression originating from the allele with a deletion (D allele) and that from the allele with an insertion (I allele) in human white blood cells from ID heterozygotes. We identified the mRNA from the I allele by using the G2215A polymorphism that lies in exon 15 and that was linked to the I/D polymorphism. RNA samples were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 25 publications
3
50
0
3
Order By: Relevance
“…The serum and tissue expression, and hence the activity of ACE, is influenced by the insertion/deletion gene polymorphism, with an increased amount of ACE mRNA originating from the D allele (30). Recently, several studies have investigated the influence of this I/D gene polymorphism on cancer risk (15, 31 -34) (33) found a significant link between the occurrence of the DD ACE gene polymorphism and the incidence of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The serum and tissue expression, and hence the activity of ACE, is influenced by the insertion/deletion gene polymorphism, with an increased amount of ACE mRNA originating from the D allele (30). Recently, several studies have investigated the influence of this I/D gene polymorphism on cancer risk (15, 31 -34) (33) found a significant link between the occurrence of the DD ACE gene polymorphism and the incidence of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The ACE I/D polymorphism is strongly associated with plasma and cellular ACE levels, and it indicates that the polymorphism may modulate the expression of the ACE gene. 11,38 Many studies found that DD genotypes and the D allele of the ACE gene were strongly associated with hypertension in different populations. [39][40][41][42][43][44][45][46] Hypertension is an important cause of ganglionic, pontine, cerebellar and lobar hemorrhages and can as well be the cause of lobar hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been considered as a functional variant, since the ACE DD genotype was associated with higher circulating [124][125][126] and tissue mRNA levels of ACE [127,128]. Among 78 variations that were found by ACE gene sequencing, 17 were in absolute linkage disequilibrium with the I/D polymorphism [129].…”
Section: Main Ras Molecules In Atherosclerosis Through the Magnifyingmentioning
confidence: 99%